Study of incidence of acute kidney injury in asphyxiated neonates with hypoxic ischemic encephalopathy - Chaudhary, Rita; Tiwari, Anil Kumar; Usmani, Farhan (International Journal of Contemporary Pediatrics, 2020)
Background: Perinatal asphyxia causes multi organ dysfunction resulting in renal (50%) and neurological (28%) compromise with 1.4% of hypoxic ischemic encephalopathy (HIE) and almost 20% death in India. Early recognition of acute kidney injury (AKI) is important in babies with HIE to facilitate appropriate fluid and electrolyte management for a stable biochemical milieu is vital. Methods: A prospective case control study was done in Patna Medical College and Hospital, Patna between January 2019 and March 2020. 70 term asphyxiated neonates with HIE as cases and 70 healthy neonates as control were taken. AKI on basis of p RIFLE criteria and HIE on the basis of 5 minute APGAR score were determined and correlated. Results: 58.6%cases of AKI with 73% pre renal and 61% non-oliguric type were found in asphyxiated neonates with HIE blood urea and serum creatinine values were significantly higher in asphyxiated babies than control group babies (p<0.0001). Conclusions: The extent of AKI is directly proportional to severity of HIE.